The dojo coach's pocket guide : maximizing immersive learning for agile teams - Brock, Jess (Berrett-Koehler Publishers, Inc., 2023)
"The go-to guidebook for helping agile practitioners overcome upskilling challenges in their organizations through effective Dojo coaching. Agile has changed the way we work in our organizations. But by demanding constant innovation and product delivery, individuals and teams struggle to find time to improve their skills. That's where the Dojo comes in. Dojo-style coaching encourages this kind of 'learn by doing' form of skill development, one where guided breakthroughs and upskilling happen while delivering on current projects. In this practical guidebook, experienced Dojo coach Jess Brock takes a deep dive into the Dojo process. Combining high-level concepts and a comprehensive toolkit, along with actionable tips needed to drive engagement in both physical and virtual Dojo spaces, you will have the tactics necessary to maximize the impact of your Dojo. Whether you are a seasoned pro or just covered the foundational concepts, this no-nonsense book will help Dojo coaches at any stage of their journey help fellow agile practitioners achieve both professional and personal growth"--